ENTREPRENEURIAL ENVIRONMENT OF RURAL WOMENENTREPRENEURS –AN OPINION SURVEY - K. Anitha and R. Chandrasekaran (DISCOURSE Xaverian Research Journal, 2018)
Entrepreneurship is a core element of growth and development for all nations. Increasing participation of women in entrepreneurship is an important part of human resource development. Women entrepreneurship is extremely low in India, especially in rural areas. Women entrepreneurship has been recognized during the last decade as an important untapped source of economic growth. This study is made to find out the opinion of rural women entrepreneurs on entrepreneurial environment. The study is based on primary data collected from 87 rural women entrepreneurs in Coimbatore. The statistical tools like Simple percentage analysis, Average score analysis and ANOVA have been used to analyze the data. It can be concluded from the results of the study that inspite of the difficulties such as increased cost of business operations faced by the rural women entrepreneurs, entrepreneurship has helped them to enhance their business skills and talents.